1994
DOI: 10.1016/0040-6090(94)90104-x
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3 coatings against high temperature corrosion deposited by metal-organic low pressure chemical vapour deposition

Abstract: Metal-organic chemical vapour deposition of thin amorphous films of Ai203 on steels was performed at low pressure. Aluminium tri-sec-butoxide (ATSB) was used as a precursor. The effects of the deposition temperature (200-380 °C), the deposition pressure (0.17-1.20 kPa) and the ATSB concentration ((5.5-33.5) x 10 -4 kPa) were studied with respect to the growth rate of the coating and the sulphidation properties at high temperatures. The sulphidation experiments were performed for 70 h at 450 °C in a gas atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Previously employed precursors to Al 2 O 3 have almost always contained an excess of oxygen (or have been used with a second oxygen source such as H 2 O). This is true in some recently reported precursors of the type Al(acac) 3 , Al(OOCR) 3 , and Al(OR) 3 (R = alkyl). These types of precursors, which were all used in the gas phase, have met with a measure of success in the fabrication of aluminum oxide thin films for use as passivating layers and insulating films in electronic devices …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previously employed precursors to Al 2 O 3 have almost always contained an excess of oxygen (or have been used with a second oxygen source such as H 2 O). This is true in some recently reported precursors of the type Al(acac) 3 , Al(OOCR) 3 , and Al(OR) 3 (R = alkyl). These types of precursors, which were all used in the gas phase, have met with a measure of success in the fabrication of aluminum oxide thin films for use as passivating layers and insulating films in electronic devices …”
Section: Introductionmentioning
confidence: 59%
“…The resulting complexes are tetrameric with a core of group 13 element and O atoms in the shape of the emblem of the Mitsubishi company. 7 They are of formula [Al{(µ-OEt) 2 AlR 2 } 3 ], where R ) Me (1), Et (2), i Bu (3), and [Al-{(µ-OEt) 2 GaR 2 } 3 ], where R ) Me (4) and Et (5). Only two such molecules, )SC 4 H 3 ) 2 } 2 AlMe 2 ] 3 ] 8 and [Al{(µ-OR) 2 AlMe 2 } 3 ] (where R ) 10-undecene), 9 have been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, MOSFET structures fabricated with Al 2 O 3 as the gate dielectric have exhibited low channel mobilities, possibly due to a large number of trapped charges in the dielectric . Furthermore, aluminum oxide thin films are applicable as corrosion and wear protective coatings, , capacitance dielectrics in DRAM's, and optical multilayer coatings …”
Section: Introductionmentioning
confidence: 99%
“…Research on the decomposition of ATSB using a quadrupole mass spectrometer (SpectraMass-Dataquad) was performed by Haanappel 16,11. It was found that the main by-products from the pyrolytic decomposition of ATSB were 2-butanol, 2-butanone, 1-or 2-butene, and n-butane.…”
Section: Mechanistic Aspects Of Oxide Deposition By Mocvdmentioning
confidence: 99%